Constituição, poder constituinte e bolivarianismo: Bolívia, Equador e Venezuela e as estratégias presidenciais - Vergueiro, João Paulo de Andrade (2013)
This dissertation studies the Andean countries of Bolivia, Ecuador and Venezuela, which have recently passed new Constitutions, under strong popular support and political renewal platforms of newly elected Presidents. The entire process of elaboration of the new Constitutions was undergone by searching popular approval, with electoral consultations to know if the constituents indeed wanted the Assemblies to be summoned up to national referendums for deliberation of the documents elaborated. To objectively understand what happened in Bolivia, Ecuador and Venezuela the literature review focused on the concepts of Constitution and Constituent power, studying also the process of elaborating Constitutions. The theoretical understanding applied to the three cases studied demonstrates the tendency of popular manipulation for the implementation of the political projects of the three elected leaders. They act, facing strong or weaker difficulties, to get the handle of the political powers of their countries, and the new Constitutions play a strong role in this project.